Understanding Digital Learning Behaviors: Moderating Roles of Goal Setting Behavior and Social Pressure in Large-Scale Open Online Courses - Zhang, Peng (Frontiers in Psychology, 2021)
This study has also been one such effort in identifying the role of digital entrepreneurship influencing sustainable digital economy, digital learning and goal setting behavior of students in China. Pandemic has changed the whole scenario worldwide, not only related to business but it has equally affected the economy as well. The things have gone online from their physical nature making it more convenient for students to learn providing online courses and lecture as per the convenience of teachers and students both. The sample used in this study was the students taking online courses through their universities. The sample size was 343 students selected through purposive sampling. Smart PLS 3.3.3 has been used for the data analysis via structural equation modeling. This study has found that technological applications play an important role in digital learning behavior which is positively moderated by goal setting behavior. Similarly intentions very much predict the digital learning behavior. Moreover, social pressure has also been found to augment the role of time flexibility in digital learning behavior. These results are very much useful for universities that make the understanding of online nature of studies more comprehensive influencing digital economic sustainability and entrepreneurship.